2019
DOI: 10.1002/ima.22348
|View full text |Cite
|
Sign up to set email alerts
|

Differences in brain networks of children with ADHD: Whole‐brain analysis of resting‐state fMRI

Abstract: The aim of this study was to investigate changes of functional connectivity (FC) in resting state networks (RSNs) in medication‐naive children with attention‐deficit/hyperactivity disorder (ADHD). Twenty children with a diagnosis of ADHD (11.8 ± 2.29 years; 16 boys) and 20 age‐matched typically developing (TD) children (13 ± 1.78 years; 10 boys) were included. It was found that brain FC differences in children with ADHD are not only in the well known RSNs such as default mode, visual, sensory motor, attentiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Structural and functional alterations in occipital were also reported in previous studies. For example, reduced gray matter volume in the right middle occipital gyrus ( Wang L. J. et al, 2020 ) and hyper-activation of occipital lobe function was found in ADHD ( Tian et al, 2008 ; Icer et al, 2019 ), indicating that atypical visual processing may play a key role. Previous study also reported that the decreased connectivity between the frontal cortex and visual cortex was associated with increased severity in ADHD symptoms ( Wang M. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional alterations in occipital were also reported in previous studies. For example, reduced gray matter volume in the right middle occipital gyrus ( Wang L. J. et al, 2020 ) and hyper-activation of occipital lobe function was found in ADHD ( Tian et al, 2008 ; Icer et al, 2019 ), indicating that atypical visual processing may play a key role. Previous study also reported that the decreased connectivity between the frontal cortex and visual cortex was associated with increased severity in ADHD symptoms ( Wang M. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analyses of rs-fMRI data consistently show significant differences in sensory areas, including the anterior cingulate gyrus, prefrontal cortex, putamen nucleus, occipital cortex, and temporal cortex in ADHD patients [ 39 , 40 ]. Additionally, low-frequency oscillations in the cerebellum and thalamus of individuals with ADHD differ significantly from those of TD individuals [ 41 ]. Abnormalities in internal functional connectivity are observed in the default network, somatosensory network, and dorsal attention network, as well as abnormal internetwork functional connectivity in the default network and ventral attention network, were present in children with ADHD and were positively correlated with ADHD symptoms [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ventral attentional network consists of the right temporoparietal connectivity and ventral frontal cortex, and it redirects attention to stimuli [ 54 ]. Correlation analysis between the sum of connectivity strengths of contributing brain regions and attention deficits revealed regions such as the right superior orbital frontal gyrus, the left rectus gyrus, and bilateral insula in multiple regions of the prefrontal lobe, the right inferior temporal gyrus and bilateral transverse temporal gyrus in temporal lobe regions, the lingual gyrus in the occipital lobe, and the left caudate nucleus [ 41 ]. This is consistent with the presence of multiple functional connectivity abnormalities in parietal and temporal brain regions in the present study and indicates that functional connectivity in parietal and temporal brain regions can be used to identify ADHD and TD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Significant negative associations were found between connectivity within the DMN, linking the ventral mPFC and right lateral parietal gyrus, ventral mPFC and right parahippocampus, and right parahippocampus and cerebellar tonsils, with hyperactive-impulsive subscale scores. Interestingly, these regions underpin decision making, self-regulation, memory and response inhibition, with the cerebellar tonsils known to play a role in visual-motor and perception, characteristic of ADHD-C clinical symptoms and proposed DMN and visual and motor networks implicated particularly to ADHD-C type ( Cao et al, 2014 ; Icer et al, 2019 ). Similarly, an inverse association of connectivity in frontal regions of the executive control network and hyperactive-impulsive symptoms in ADHD-C has been previously reported ( Elton et al, 2014 ; Francx et al, 2015 ; Pruim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%